2007
DOI: 10.1016/j.jim.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Improved anti-IgG and HSA affinity ligands: Clinical application of VHH antibody technology

Abstract: Large scale, highly specific purification of valuable proteins from blood and removal of undesirable components promise to have wide therapeutic applications. Moreover, depletion of bulk proteins from blood is a prerequisite for clinical proteomics. Here we describe the development of specific, high affinity Camelid antibody fragments (VHH) derived from immune libraries for purification and depletion of the bulk protein HSA and IgG from human serum and plasma for therapeutic and research purposes. The anti-IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…3). Altogether, these data demonstrated that the two anti-idiotype VHHs specifically recognized the CDRs of their targets with affinities allowing their capture as well as their elution21.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…3). Altogether, these data demonstrated that the two anti-idiotype VHHs specifically recognized the CDRs of their targets with affinities allowing their capture as well as their elution21.…”
Section: Resultsmentioning
confidence: 72%
“…Thus, the physical and thermal stability, or better, the capacity of VHHs to refold completely after denaturation enables the apparent infinite reusability of the columns15. These characteristics explained that these binding domains have already been successfully applied as affinity ligands in chromatography processes covering a variety of biotherapeutics16171819, can serve as target-specific capture reagents20, and can replace the conventional and expensive protein A purification step2122.…”
mentioning
confidence: 99%
“…In addition to the immunodepletion of TSST-1 from human plasma, we believe that these columns can be equipped with other ligands in order to deplete other contaminants from plasma. Consistently, a VHH has been recently discovered which can be used to deplete the bulk plasma protein IgG (Klooster et al, 2007). This VHH display improved depletion over the classical method based on protein A depletion, and the authors concluded that the VHH can be used for antibody depletion in the auto-immune diseases Goodpasture's syndrome and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3] For example, antihuman IgG VHH has been developed for IgG purification and depletion from blood, outperforming canonical protein A-based method. 38 Apart from concave epitopes on properly folded proteins, nanobodies could recognize small linear peptide sequences, which has been confirmed by isolating anti-EPEA VHHs. EPEA is a C-terminal tetra-amino-acid Glu-Pro-Glu-Ala sequence that can be cloned as a tag behind any protein, 39 facilitating a rapid and robust affinity purification of proteins.…”
Section: Nanobodies As Versatile Research Tools In Biotechnologymentioning
confidence: 84%